2019
DOI: 10.21608/jhiph.2019.56578
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Indices among Secondary School Students in Assiut Governorate; Upper Egypt

Abstract: Background & Objective(s):There is limited published data on Egyptian oral epidemiologic health status especially among adolescents. This study aimed to evaluate oral health status and their associated variables among secondary school students in Assiut Governorate; Upper Egypt. Methods: : A cross sectional study was conducted on 872 students using a representative sample from public, private and technical secondary schools. Data were collected using a self-administered questionnaire including inquires about s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…In our study we found that 60 % of female's students had a good oral hygiene because 52.50 % brush their teeth twice and 56.25% brush for 5 minutes. This finding was in agreement with study done by Mohamed Edrees et al ,in Egypt which found that 59.3% of the students perceived their oral health as good or very good, because 25.6% brush twice and 41% brush more than 2 minutes , only 10% used inter dental aids which is dental floss (9). Also in our study we found that more than half used inter dental aids mainly interdental brush this reflect their good awareness regarding their important in inter proximal plaque and food removal which preventing gingival and periodontal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…In our study we found that 60 % of female's students had a good oral hygiene because 52.50 % brush their teeth twice and 56.25% brush for 5 minutes. This finding was in agreement with study done by Mohamed Edrees et al ,in Egypt which found that 59.3% of the students perceived their oral health as good or very good, because 25.6% brush twice and 41% brush more than 2 minutes , only 10% used inter dental aids which is dental floss (9). Also in our study we found that more than half used inter dental aids mainly interdental brush this reflect their good awareness regarding their important in inter proximal plaque and food removal which preventing gingival and periodontal diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, daily flossing by Iranian students was reported by Pourhaji et al, [31] and Soltani et al, [27] to be 44.8 and 31%, respectively. Compared to other countries, the rate was 19.6% in a study by Farsi in Saudi Arabia [32], 13.1% in Japan [33], 7.3% in Nigeria [34], and 10.6% in Egypt [35].…”
Section: Discussionmentioning
confidence: 80%